(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione - 2. L’accomodamento ragionevole: cenni - 3. Dalla laicità come metodo alla reasonable accommodation - 4. (segue) Limiti e aporie - 5. Spunti conclusivi. Religious symbols and reasonable accommodation ‘all’italiana’ in the recent jurisprudence of legitimacy ABSTRACT: With the judgment no. 24414/2021, the United Sections of the Court of Cassation identified reasonable accommodation as a possible solution to the issue of religious symbols in public school classrooms. The application of the instrument (traditionally used to protect freedom of religion and belief in the workplace) to the case at hand is undoubtedly characterized by original features that this paper aims to analyze. After having reconstructed the model of reasonable accommodation proposed by the Court, this article tries to verify whether the use of this instrument can be effective and applicable, from a technical-legal point of view, even in the public-school context, which involves principles endowed with axiological primacy, such as that of ‘laicità’. Brief concluding remarks will be addressed to the possible effects of this ruling in those areas of Law and Religion which are characterized by regulatory gaps and/or a high degree of conflict.